Sexual Knowledge and Attitudes Among Premarital Couples: A Need for Future Educational Programs - Sadat; Ghofranipour; Goshtasebi; Azin (Kashan University of Medical Sciences, 2016)
Background A significant number of youths have insufficient awareness about sexual health; whereas, correct sexual information is the main factor to prevent adverse consequences. Objectives The current study aimed to investigate the sexual knowledge and attitudes in a sample of Iranian premarital couples. Patients and Methods In this cross-sectional study, a sequential sample of 500 males and females who met the inclusion criteria was selected. This study was conducted in Kashan, Iran. Participants were in the age range of 16 to 40 years referred for premarital testing and educational classes. Two questionnaires containing demographic data and a culturally based sexual knowledge and attitudes scale were used for data collection. Data were analyzed using the Chi-square test, independent samples t-test, Mann-Whitney U, analysis of variance and multivariate regression. Results About 50% of premarital couples had poor sexual knowledge and attitudes. The mean score of total sexual knowledge was 12.45 ± 8.54 out of a possible score of 33; and the mean score of total sexual attitudes was 121.63 ± 14.51 out of a possible score of 170. A significant association existed between the score of sexual knowledge and the level of education (P < 0.01), participants' age (P < 0.01) and the score of sexual attitudes (P < 0.01). Conclusions The majority of participants had poor sexual knowledge and attitudes regarding different aspects of sexual health.